2020
DOI: 10.1038/s41422-019-0233-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of nucleic acid recognition and 6mA demethylation by human ALKBH1

Abstract: Dear Editor, DNA N 6-methyladenine (6mA) modification is common in prokaryotes 1 and eukaryotes, 2 involving in gene regulation, transposon, stem cell differentiation, and human tumors. At

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…Despite that ALKBH1 has recently been reported as a 6mA demethylase (Xiao et al, 2018;Xie et al, 2018), which is by far the only one identified in human, we did not observe discernible difference in the 6mA levels in hESCs, hMSCs or hVSMCs caused by ALKBH1 deficiency, consistent with the recent report that ALKBH1 fails to eliminate 6mA in mESCs or HEK293T cells (Liu et al, 2020). Given that two studies have shown that ALKBH1 preferably demethylates 6mA on unpaired DNAs (Tian et al, 2020;Zhang et al, 2020a), our results imply that there might be few unpaired DNAs in the normally cultured hESCs, hMSCs and hVSMCs. For example, R-loop, a form of unpaired DNAs, is a known ALKBH1 substrate that only accounts for about 5% of the human genome (Sanz et al, 2016;Zhang et al, 2020a).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Despite that ALKBH1 has recently been reported as a 6mA demethylase (Xiao et al, 2018;Xie et al, 2018), which is by far the only one identified in human, we did not observe discernible difference in the 6mA levels in hESCs, hMSCs or hVSMCs caused by ALKBH1 deficiency, consistent with the recent report that ALKBH1 fails to eliminate 6mA in mESCs or HEK293T cells (Liu et al, 2020). Given that two studies have shown that ALKBH1 preferably demethylates 6mA on unpaired DNAs (Tian et al, 2020;Zhang et al, 2020a), our results imply that there might be few unpaired DNAs in the normally cultured hESCs, hMSCs and hVSMCs. For example, R-loop, a form of unpaired DNAs, is a known ALKBH1 substrate that only accounts for about 5% of the human genome (Sanz et al, 2016;Zhang et al, 2020a).…”
supporting
confidence: 85%
“…6mA has been reported to associate with multiple physiological processes including embryonic development and tumorigenesis (Greer et al, 2015 ; Zhang et al, 2015 ; Xie et al, 2018 ), yet some controversies exist. In contrast to the findings showing that ALKBH1 (alkB homolog 1) is a primary 6mA demethylase in mouse and human cells (Wu et al, 2016 ; Xiao et al, 2018 ; Xie et al, 2018 ), other studies indicate that ALKBH1 is prone to demethylate 6mA on bubbled or bulged DNAs that are often featured by a locally unpairing region with flanking duplex, such as D-loop, R-loop as well as DNA or RNA stem-loop, and single-stranded DNAs at a lower efficiency, but not double-stranded DNAs (Tian et al, 2020 ; Zhang et al, 2020a ). Stem cell exhaustion is a major causal and risk factor underlying the progressive disruption of physiological integrity during the development of aging-associated disorders, in which epigenetic alterations are closely implicated (Zhang et al, 2020b ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To generate Alkbh1 KO mice, we used the CRISPR/ Cas9-mediated exon skipping approach in inbred C57BL/6N zygotes. We expected complete disruption of Alkbh1 function by introducing frameshift mutations into exon 4, because exons 4-6 encode functional domains [19]. Therefore, we focused on exon 3 as an exon-skip target and designed two sgRNAs in the introns on both sides of exon 3 (Fig.…”
Section: Generation Of the Whole-body Alkbh1 Ko Micementioning
confidence: 99%
“…Furthermore, mammalian ALKBH1 demethylates m 5 C derivative intermediates on the tRNAs as well in various cellular compartments (Kawarada et al, 2017 ). More recently, it was confirmed that ALKBH1 could also demethylate N6-methyladenine (m 6 A) on DNA, suggesting dual important epigenomic regulatory roles in DNA and epitranscriptomic roles on various forms of RNAs (Tian et al, 2020 ; Zhang et al, 2020 ). Although ALKBH-2 and−3 promote both m 1 A and 3-methylcytidine (m 3 C) demethylation, ALKBH2 efficiently repairs both methylated single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA), whereas ALKBH3 preferentially demethylates single-stranded nucleic acids (Monsen et al, 2010 ).…”
Section: Introductionmentioning
confidence: 96%